A Six-Week Plyometric Training Program Improves Explosive Power and Agility in Professional Athletes of East Java - Dwinda Abi Permana; Nining Widyah Kusnanik; Nurhasan Nurhasan; Slamet Raharjo (OVS LLC, 2022)
The study purpose was to prove the effectiveness of a plyometric training program in increasing explosive power and agility in professional athletes of East Java. Materials and methods. This study is a pre-experiment with a research design of One Group Pretest-Posttest. A total of 15 male athletes from athletics and swimming at the Pusat Pendidikan dan Pelatihan Olahraga Pelajar (PPLP) East Java, Indonesia, aged 15-17 years, body mass index (BMI) 18.5-24.0 kg/m², normal blood pressure, normal resting heart rate, voluntarily participated in the study. The plyometric training program (hurdle-box jumps) was carried out for 30 minutes/training session with an intensity of 80-90% HRmax with a frequency of 3x/week for six weeks. Measuring the explosive power of the horizontal leg muscles used the Standing Broad Jump Test, while measurement of the explosive power of the vertical leg muscles used the Digital Jump Meter Test. Measurement of agility used Shuttle Run Test, and explosive power and agility were measured during pre-training and six weeks post-training. Data analysis used the Paired Sample T-Test with a significance level of 5% using the Statistical Package for Social Science (SPSS) version 21 software. Results. The results of the study showed that there was a significant difference in the average increase in explosive power horizontally, vertically, and agility between pre-training vs. post-training (p ≤ 0.001). Conclusions. In general, it can be concluded that the plyometric training program (hurdle-box jumps) carried out 3x/week for six weeks effectively increases the explosive power of the horizontal leg muscles, the explosive power of the vertical leg muscles, and increases agility.